2017
DOI: 10.31807/tjwsm.297212
|View full text |Cite
|
Sign up to set email alerts
|

First Biological Monitoring in the Akarçay Basin According to the Water Framework Directive: Phytoplankton and Phytobenthos

Abstract: In this study, it was aimed to investigate of phytoplankton and phytobenthos in 19 rivers and Lake Eber for the assessment of ecological quality in the Akarçay basin. A total of 63 phytoplankton species were identified. Phytoplankton was evaluated according to sensitive species and pollution indicators in rivers. Lake Eber was determined as eutrophic and sensitive area according to phytoplankton functional groups and Q Index. The presence of phytobenthic macroalgae was detected only some sampling points in riv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Some studies were carried out in order to classify the water quality by using diatom indices in Turkey (Kalyoncu et al, 2009;Kıvrak et al, 2012; Morkoyunlu Yüce and Gönülol, 2016; Atıcı et al, 2018). In addition, other studies are also available which evaluate the phytobenthos for each river basin (Demir et al, 2017;Toudjani et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies were carried out in order to classify the water quality by using diatom indices in Turkey (Kalyoncu et al, 2009;Kıvrak et al, 2012; Morkoyunlu Yüce and Gönülol, 2016; Atıcı et al, 2018). In addition, other studies are also available which evaluate the phytobenthos for each river basin (Demir et al, 2017;Toudjani et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this research, diatom composition and its distribution through the streams, lakes and reservoirs of the basin were studied for the first time in detail, and the diversity was found relatively higher in comparison with different river basins. Solak et al (2018) found 94 taxa from Küçük Menderes River Basin, Çelekli et al (2018) reported 80 taxa from the North Aegean catchment while 148 taxa reported from western Black Sea River catchment (Özer et al, 2018) and Demir et al (2017) observed 64 diatom taxa from Akarçay River Basin. Similarly, 65 diatom taxa were found in Aras River catchment (Çelekli et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Their prompt response to the environmental changes and their presence throughout the year together with rapid reproduction stages made diatoms an essential tool for monitoring freshwater systems. Studies were conducted in various waterbodies of Turkey to detect the environmental quality of the lakes (Dalkıran et al 2016;Şanal & Demir, 2018) and rivers (Atıcı, 1997;Karacaoğlu & Dalkıran, 2017;Demir et al 2017;Solak et al 2018;Çelekli et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Phytoplankton, macrophyte and phytobenthos, benthic invertebrates and fish are the biological quality elements for the classification of ecological status (Anonymous, 2000). There are some studies (Demir et al, 2017;Çelekli et al, 2018;Solak et al, 2018a) for identifying the ecological status of water bodies in Turkey within the scope of the river basin based monitoring studies.…”
Section: Introductionmentioning
confidence: 99%